Gambaran Agresivitas Suporter Sepakbola di Kota Kudus - Cahya, Tarindra (Journal of Psychology and Treatment, 2022)
Supporter appears as a form of spirit and also become a character of each team. Supporter can be as a cause of the ruin from the team also. The objective of this research is to know the form of the aggressive from Kudus team supporter and to know the factors that influence the aggressive of Kudus team supporter. The research method of this research is qualitative method and the collecting data technique by using interview. The analysis technique of this research using descriptive narrative technique. The result of this research is that the most influence from the agresivity are alcohol and drugs because the supporter will be easier because of their unconscious mind.